Knowledge Management Transformation in Pesantren: A Case Study of Pondok Pesantren Darul Ulum Jombang - Zulkifli Syauqi Thontowi; Riski Eka Purnairawan; Iqbal Faza Ahmad (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to analyze the transformation of knowledge management at Pondok Pesantren Darul Ulum (PPDU) Jombang. The primary focus of this study is to address how pesantren institutions maintain salaf (traditional) values while adopting national educational professionalism systems. Methods – This research employs a qualitative approach with a case study design. Data were collected through participatory observation in dormitory and school environments, institutional archival documentation, and in-depth interviews with the Board of Pesantren Leadership (Majelis Pimpinan Pondok Pesantren), heads of educational units, administrative staff, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing to validate the knowledge management cycle. Findings – The results indicate that PPDU's institutional transformation is divided into three phases: traditional, transitional, and modern. Key findings reveal that knowledge management is implemented through the integration of the Kitab Kuning (classical Islamic texts) curriculum with the national curriculum. Technically, the institution has codified tacit knowledge into explicit knowledge through the digitalization of student databases and the formulation of formal SOPs. The acceleration of transformation is driven by the collective leadership of the MPPK, which effectively mitigates human resource competency gaps and technological infrastructure constraints. Research Implications – The implications of this research emphasize the importance of an adaptive knowledge management model for the sustainability of pesantren in the disruption era. The limitation of this study lies in its focus on a single site (single case study), so the generalizability of the findings may be limited to pesantren with similar organizational characteristics.